Germanium Quantum Dot Grätzel‐Type Solar Cell. Issue 24 (15th October 2018) - Cardoso, Jonathan; Marom, Sarita; Mayer, Justin; Modi, Ritika; Podestà, Alessandro; Xie, Xiaobin; van Huis, Marijn A.; Di Vece, Marcel
Abstract : Solar cells fabricated from sustainable quantum dot materials are currently not commercially available, but ongoing research provides a steady increase in efficiency and stability of laboratory devices. In this work, the first germanium quantum dot solar cell made with a gas aggregation nanoparticle source is presented. UV–vis spectroscopy reveals quantum confinement, and the spectral response of the germanium quantum dot Grätzel‐type solar cell confirms the presence of large and small band gap optical absorption due to a mix of particle sizes. Some of the particles are small enough to have substantial quantum confinement while others are so large that they have bulk‐like properties. The efficiency of the germanium quantum dot solar cells is very low but could reach 1% if the formation of germanium oxide layers is avoided in future experiments. This first quantum dot solar cell made with a gas aggregation nanoparticle source demonstrates, as a proof of concept, the technological potential for research and applications combining the fields of photovoltaics and gas aggregation nanoparticle sources. Abstract : A proof of concept germanium quantum dot Grätzel‐type solar cell is fabricated with a magnetron sputtering gas aggregation nanoparticle source. The efficiency of the germanium quantum dot solar cells is very low but could reach 1% if the formation of germanium oxide layers is avoided in future experiments.